TARO BENENG CHIP BUSINESS MANAGEMENT TRAINING AT TUNAS MANDIRI CINYURUP PANDEGLANG FARMER GROUP: PELATIHAN MANAJEMEN USAHA KERIPIK TALAS BENENG PADA KELOMPOK TANI TUNAS MANDIRI CINYURUP PANDEGLANG - Icin Quraysin; Efi Tajuroh Afiah (Yayasan Education and Social Center, 2021)
The Tunas Mandiri farmer group in the Cinyurup village is a group of residents, some of whom are mothers, who manage the taro beneng chips business, but the management is still simple and not managed systematically and well planned, so it has not been able to provide maximum results. The purpose of this training to increase competitiveness for small and medium-sized industrial entrepreneurs of taro beneng chips towards independent small industries. The implementation method is through: seminars for delivering material, discussions, practices, mentoring, monitoring and evaluation. The results of this training show that independent tunas farmer groups are managing the taro beneng chips business in Cinyurup village, has not been able to manage the business properly, has not taken care of distribution permits, halal certificates, produces product innovations and online marketing, due to limited funds and human resources.